Archaea show different geographical distribution patterns compared to bacteria and fungi in Arctic marine sediments - Jianxing Sun; Hongbo Zhou; Haina Cheng; Zhu Chen; Yuguang Wang (mLife)
Abstract Microorganisms dominate marine environments in the polar oceans and are known to harbor greater diversity and abundance than was once thought, and yet, little is known about their biogeographic distribution patterns in marine sediments at a broad spatial scale. In this study, we conducted extensive sampling of marine sediments along a latitudinal transect spanning 2500 km from the Bering Sea to the Arctic Ocean to investigate the geographical distribution patterns of bacteria, archaea, and fungi. Our findings revealed that the community similarities of bacteria and fungi decay at similar rates with increasing geographical distance (slope: −0.005 and −0.002), which are much lower than the decay rate of archaeal communities (slope: −0.012). Notably, microbial richness and community composition showed significant differences in the region of 75−80°N compared to other regions in 60−75°N. Salinity, temperature, pH, ammonium nitrogen, and total organic carbon are key factors that significantly affect microbial community variations. Furthermore, bacterial co‐occurrence networks showed more complex interactions but lower modularity than fungal counterparts. This study provides crucial insights into the spatial distribution patterns of bacteria, archaea, and fungi in the Arctic marine sediments and will be critical for a better understanding of microbial global distribution and ecological functions.